2013
DOI: 10.1016/j.idairyj.2012.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat and pH on structure and conformation of whey proteins

Abstract: Please cite this article as: Dissanayake, M., Ramchandran, L., Piyadasa, C., Vasiljevic, T., Influence of heat and pH on structure and conformation of whey proteins, International Dairy Journal (2012), doi: 10.1016/j.idairyj.2012.08.014. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 16 publications
4
34
0
Order By: Relevance
“…The results obtained are in agreement with other previous observations on thermal denaturation of whey proteins either in isolated, admixture form or in skimmed milk (Mainer et al 1997;Dissanayake, Ramchandran, Donkor et al 2013;Dissanayake, Ramchandran, Piyadasa et al 2013). Different methods have been applied to study heat stability of bovine IgG in different matrices.…”
Section: Effect Of Heat On Igg and Lf Concentration In Liquid Whey Wisupporting
confidence: 90%
“…The results obtained are in agreement with other previous observations on thermal denaturation of whey proteins either in isolated, admixture form or in skimmed milk (Mainer et al 1997;Dissanayake, Ramchandran, Donkor et al 2013;Dissanayake, Ramchandran, Piyadasa et al 2013). Different methods have been applied to study heat stability of bovine IgG in different matrices.…”
Section: Effect Of Heat On Igg and Lf Concentration In Liquid Whey Wisupporting
confidence: 90%
“…Figure 2 showed DSC curve recorded (at a heating rate of 1.0 o C/min) for PWP at pH 8.5. The physicochemical pr operties of whey proteins present as well as intrinsic (structure and conformation) including Van der Waals and steric forces, different attractive or repulsive molecular forces, and extrinsic (environment) conditions including pH, temperature, ionic strength, solvent polarity and type, govern the whey protein functionality [Dissanayake et al, 2013].…”
Section: Effects Of Heating Time and Homogenization Pressure On Eai Omentioning
confidence: 99%
“…During heat treatment, whey protein undergoes denaturation and some structural changes. [15,16] Studies have revealed that, due to unfolding by preheating treatment of whey protein, improved functional and encapsulation properties such as gelation and adsorption at the interface have been reported. [17][18][19][20] Whey protein has also proved to be an effective encapsulating agent because of its ability to form microcapsules easily under mild conditions using different techniques.…”
Section: Introductionmentioning
confidence: 99%